Berufliche Bildung und berufliche Handlungskompetenz im Abseits politisch-ökonomischer Reflexion. Eine Polemik in konstruktiver Absicht und Wolfgang Lempert zum Gedenken - Kutscha, Günter [Verfasser] (My University, 2018)
""Menschlichkeit der Technik" (Blankertz), "Leistung und Emanzipation" (Lempert), diese Themen waren für die Ideengeber der emanzipatorischen Berufs- und Wirtschaftspädagogik von zentraler Bedeutung. Heute gehören sie im berufsbildungswissenschaftlichen Diskurs eher zum Schnee von gestern. Und das, obwohl Berufsbildungspolitik und -praxis angesichts der Herausforderungen durch nicht kontrollierbare technologische Dynamik und diese antreibenden Kapitalverwertungsdruck mit der Frage konfrontiert ist, wie die nachwachsende Generation auf eine Welt vorbereitet werden kann, von deren potenziellem Zerfall sie bedroht ist. Die Berufs- und Wirtschaftspädagogik drückt sich weithin um diesen Fragenkomplex herum und betrachtet die zunehmend digitalisierte Arbeitswelt, so wie sie nun mal ist, als normative Kraft des Faktischen. Sie konzentriert sich auf Theorie, Forschung und Praxis der Vermittlung und Aneignung beruflicher Handlungskompetenzen als Surrogat für berufliche Bildung. Dabei bleibt außen vor, dass berufliche Kompetenzentwicklung Teil der kapitalbasierten Maschinerie und des darauf fixierten Wertesystems ist. Jedenfalls entzieht sich die Berufs- und Wirtschaftspädagogik als bodenständige Disziplin nüchtern betrachtet einer radikalen Neubesinnung ihrer "einheimischen" Begrifflichkeiten und Forschungsarbeiten." (Textauszug; BIBB-Doku)

"The humanity of technology, work and emancipation were topics of central importance to the initiators of emancipatory vocational and business education in Western Germany (Blankertz, Lempert). Today they are rather old news in the theoretical discourse of vocational and economic education. VET science focuses on theory, research and practice of acquiring professional skills without considering that these are part of the capital-based, overall political-economic context. Vocational competence is characterized economically by its usability in the production of goods and services and in this way by its impact on the productivity of work for the benefit of return on assets. The characterization of occupational competencies as a commodity is discussed in part 1, using the example of vocational training in retail. Part 2 discusses the ideology of equating vocational competence on the one hand and vocational education on the other within the framework curricula for vocational education arranged by the Federal Länder Coordination Committee for Vocational Training Regulations. Specific to the concept of emancipatory vocational education is the dimension of critical reflection, in particular the political-economic and societal reflection of work experience in training companies. This is explained in more detail in part 3, which refers to the educational theory and research concepts of Herwig Blankertz and Wolfgang Lempert. Finally, part 4 takes a critical look at the difficulties that prevent vocational schools in Germany's Dual System of vocational education and training from fulfilling their educational mission, combined with vocational competence and beyond. This part refers to the so-called "modernization" of the Vocational Training Act. The actual amendment of the current law is considered as an example of the reform policy called "Continuity in Change". This is especially true for the final examinations that are the responsibility of the chambers of commerce and industry, and the chambers of crafts. These examinations in the dual training system are not only geared to the requirements of the training companies, but also greatly influence the teaching in vocational schools. There seems to be no alternative to the subjection of vocational education to the hegemony of global finance and digital technology. There is also, therefore, no alternative apart from the ability of radical criticism. As the author sees it, this is still, more than ever, the potential of emancipatory vocational and business education according to the ideas of Herwig Blankertz and Wolfgang Lempert." (author's abstract; BIBB-Doku)
Vocational education and professional competence out of political-economic reflection. A polemic in constructive intent in memory of Wolfgang Lempert
Keywords: T 4.9 Pädagogik; S 2.4.1 Lernortkooperation; Berufspädagogik; Wirtschaftspädagogik; Handlungskompetenz; Begriff; Kaufmann im Einzelhandel; Berufsschule; Ökonomisierung; Blankertz, Herwig